2017
DOI: 10.24838/ip.2017.v70.i1.48997
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of <I>Rhizoctonia solani</I> AG 1-IA on Major Weeds Prevalent in Rice and Maize Ecosystem in Meghalaya

Abstract: Rhizoctonia solani Kühn (Teleomorph: Thanatephorus cucumeris) is an economically important soil borne basidiomycetous pathogen of worldwide distribution. It causes sheath blight disease of rice and banded leaf and sheath blight (BLSB) disease in maize. Twenty three lowland rice weeds and thirty one upland (maize) weeds were collected and used. Rice isolate (SRS) was pathogenic on all the lowland rice and upland weeds. Maize isolate (RSM2) was not pathogenic on Cyperus difformis, C. haspans, C. odoratus, Sagitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Kannaiyan and Prasad (1979) have also reported that R. solani occured on 21 weed hosts and it was severe on weeds like Eriochloa procera, Andropogon asper, Cynodon dactylon and Ischaemum indicum. Saveinai et al (2017) did similar kind of work on pathogeniticity of R. solani AG 1-IA on weeds and results showed that isolate SRS (isolated from rice) was pathogenic on all the weeds and isolate RSM2 (isolated from maize) was found to be pathogenic on all weeds except Cyperus difformis, C. haspans, C. odoratus, S. sagittifolia, Celosia argentea, Commelina diffusa and F. miliacea. In our findings, R. solani AG 1-IB (isolated from soybean) was pathogenic on all the weeds.…”
Section: Pathogenicity Of Rhizoctonia Solani Ag 1-ib On Common Weedsmentioning
confidence: 94%
See 4 more Smart Citations
“…Kannaiyan and Prasad (1979) have also reported that R. solani occured on 21 weed hosts and it was severe on weeds like Eriochloa procera, Andropogon asper, Cynodon dactylon and Ischaemum indicum. Saveinai et al (2017) did similar kind of work on pathogeniticity of R. solani AG 1-IA on weeds and results showed that isolate SRS (isolated from rice) was pathogenic on all the weeds and isolate RSM2 (isolated from maize) was found to be pathogenic on all weeds except Cyperus difformis, C. haspans, C. odoratus, S. sagittifolia, Celosia argentea, Commelina diffusa and F. miliacea. In our findings, R. solani AG 1-IB (isolated from soybean) was pathogenic on all the weeds.…”
Section: Pathogenicity Of Rhizoctonia Solani Ag 1-ib On Common Weedsmentioning
confidence: 94%
“…Experiments related to "Pathogenicity of R. solani AG 1-IB on common weeds in Meghalaya" were conducted at ICAR Research Complex for NEH Region, Umiam, Meghalaya during 2016-2017. Infected soybean samples exhibiting web blight symptoms were collected from experimental plots of ICAR, Umiam and isolation was done following the method as described in Saveinai (2016) PCR was used for amplification of extracted DNA with specific primers for AG 1-IA and IB (Matsumoto 2002 andSayler andYang 2007). Both positive and negative controls were also used.The DNA extraction, PCR (with minor modifications), gel documentation and identification was done following the procedure described by Mahendra et al (2016).One isolate (PPJ3) was also amplified and Highly susceptible weeds identified in this study should be avoided for mulching purpose since this will increase the inoculum load of this pathogen sequenced by using universal primers for ITS region (ITS 5 and 4) (White et al 1990) and the sequence was deposited in Genbank.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations